THE RELATIONSHIP BETWEEN ONLINE GAMBLING BEHAVIOR WITH EMOTIONAL DISORDERS OF COLLEGE STUDENT - Lubis, Ayu Hayati; Mardianto (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Many college students were involved in online gambling games, and there is a tendency to this student to show excessive emotional responses when playing online gambling that leads to emotional disorders. Therefore, this research aims to find out the relationship between online gambling behavior with student emotional disorders. This research is a quantitative correlation type research. Data collection techniques in this research were online gambling and emotional disorders scale. The research subjects of this study were 385 college student of Padang State University. The sampling technique uses purposive sampling. The data analysis technique used is product moment analysis. The research results show that emotional disturbances of college students who play online gambling games are in the moderate category (54.0%) with the most determining aspect is learning problems. Which means, the college students who have high emotional disturbances will have high learning problems. Meanwhile, online gambling behavior of college students are in the moderate category (64.9%) with the most determining aspect is escapae. Which means, college students performed online gambling behavior due to they use online gambling as a place to escape from problems or to spend their free time. The correlation test found that there was a significant relationship between online gambling behavior and college students' emotional disorders because the Sig value obtained was 0.00 (p <0.05). The relationship that is formed has a positive slope, which means that the higher the online gambling behavior of college students, the higher their emotional disturbances.